A STUDY ABOUT DESIGN THINKING APPLIED TO THE BUSINESS MODEL - Araújo, Liriane Soares; Fernandes Gentil , Ederson; Bertuci, Matheus Henrique (Revista Interface Tecnológica, 2021)
Companies from all over the world are looking for innovation and improvements in their processes, products or services. In this sense, Design Thinking has proven to be a very efficient methodology in extracting insights for understanding problems within organizations, adding greater value to the business. This work presents a review of successful cases using the principles of Design Thinking, covering a descriptive and exploratory bibliographic research of an applied nature with a qualitative approach. As a result, we present the cases and ideas of changes that were applied in organizations when using this methodology in the business model, in order to assist companies in its use.